A Five-Year Epidemiological Analysis of Mandible Fractures in Bali - Kawilarang, Bertha; Sanjaya, I Gusti Putu Hendra; Hamid, Agus Roy Rusly Hariantana (The Lingkar Studi Bedah Plastik Foundation and is affiliated with the Department of Plastic Surgery, Faculty of Medicine, Universitas Indonesia., 2025)
Introduction: This study aims to assess the prevalence, sociodemographic factors, and patterns of mandible fractures at Prof. dr. I.G.N.G. Ngoerah General Hospital, recognizing that more than half of all maxillofacial injuries are due to mandible fractures, attributable to the mandible's prominent structure.Methods: This retrospective study was held in Prof. dr. I.G.N.G. Ngoerah General Hospital. Data were collected from January 2018 to December 2023. A total of 289 samples were included in this study. Age, gender, anatomical location of the fractures and unilateral/bilateral involvement were reported. Results: During the period spanning January 2018 to December 2023, a comprehensive analysis of 289 mandible fracture cases was conducted. Notably, the highest incidence was observed in 2022, comprising 72 cases. Predominantly affecting males (72.7%) within the age bracket of 21-30 years (40.1%), these fractures were primarily attributed to road traffic accidents (64.4%), often associated with alcohol influence (43.9%). Remarkably, non-helmet usage was prevalent among the majority of patients (69.9%), particularly motorcycle drivers (53.3%). The parasymphysis region emerged as the most frequently affected area (38.1%), with unilateral involvement prevailing in the majority of cases (61.6%). Additionally, associated injuries were noted in 88.5% of cases, with management predominantly comprising open reduction internal fixation (ORIF) complemented by maxillomandibular fixation (MMF) in 66.8% of cases.Conclusions: The findings of this study reveal a progressive rise in the annual incidence of mandible fractures. Consequently, there is a pressing need to heighten awareness among healthcare practitioners when managing patients presenting with maxillofacial traumas.